Answer:
y = -3x + 7
Explanation:
To start with the slope, given by two points on the graph:
(0, 7) and (1, 4):
Let x1 = 0
x2 = 1
y1 = 7
y2 = 4
We can use the following slope formula:
![m = ((y_(2) - y_(1)))/((x_(2) - x_(1))) = (rise)/(run)](https://img.qammunity.org/2022/formulas/mathematics/college/hqvps9d8esan1nojflt0vmuvjyo6hls65t.png)
![m = ((4-7))/((1-0)) = (-3)/(1) = -3](https://img.qammunity.org/2022/formulas/mathematics/college/mmohsozyv5uyvoy2uohxb5fckdmxphk445.png)
It is a negative slope because it is sloping downwards.
Now that we have our slope, we can move on to the y-intercept, ( b ). The y-intercept is the value of y when the value of x = 0. Looking at the graph, we can see that the y-intercept is (0, 7). It is usually the point where it touches the y-axis.
Now that we have our slope (m ) and y-intercept ( b ), we can establish our linear equation in the slope-intercept form, y = mx + b:
y = -3x + 7